Desain dan Pengembangan Aplikasi Pengelolaan Properti Mode Offline Menggunakan Sinkronisasi Otomatis dan CQRS Event Sourcing - Muhammad Ariq Hawari Adiputra; Made Hanindia Prami Swari; Afina Lina Nurlaili (bit-Tech, 2026)
The advancement of information technology has accelerated the digitization of project management, particularly in the supervision and monitoring of construction progress previously handled manually through paper-based documents and Excel spreadsheets. Such manual processes have led to delays in reporting, data duplication, and reduced data accuracy. This study aims to design and implement a web- and mobile-based project management and property sales system featuring Offline-First Synchronization, Command Query Responsibility Segregation (CQRS), and Event Sourcing to maintain the integrity of progress data and empower field supervisors to operate without an internet connection. The research method follows the waterfall model, comprising needs analysis, system design with a clear separation of command and query, and the implementation of event log storage as the single source of truth for every data change, using Laravel as the backend and React Native with MMKV for local storage. Testing results demonstrate that the system ensures data consistency through automatic synchronization once network connectivity is available and can reconstruct project development progress using stored event data. Performance benchmarking showed that CQRS bulk operations reduced processing time to 0.053 seconds, outperforming traditional CRUD bulk operations at 0.073 seconds, while query latency in event sourcing read models averaged 0.101 seconds, only slightly higher than 0.089 seconds in direct database queries. The system also achieves reliable auditability and supports efficient task update and historical recalculation via event replay. The findings confirm that applying CQRS and Event Sourcing within an offline-first architecture improves reliability, auditability, and efficiency in field project monitoring.